Gamification Strategies at the Service of Knowledge Management: Gestión del conocimiento y gamificación organizacional - Valencia Quecano, Lira Isis (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This research aims to analyse the implementation of gamification strategies in the knowledge management model at the organisational level. As a methodology, a literature review was conducted by analysing the identification and transmission of knowledge, media and technology, decision-making, organisational culture, and competence. 50 articles on the use of gamification and knowledge management were obtained. The results identify its contribution to the appropriation, socialisation, and transfer of knowledge in human capital. Finally, it is identified that gamification facilitates the processes related to the knowledge management model in organisations.